Criminological Analysis of Women's Involvement in Class I Narcotics Trafficking Crimes: (Empirical Study in the Jurisdiction of the Tanah Datar Police) - Mila Haida; Syaiful Munandar (Jayapangus Press, 2026)
Class I narcotics trafficking constitutes a serious crime with far-reaching impacts on public health, social stability, and national security. In recent years, the jurisdiction of the Tanah Datar Police has shown an increasing involvement of women as perpetrators of narcotics trafficking, indicating a shift in crime patterns as well as the presence of gender-specific vulnerabilities. This study aims to analyze the criminological factors underlying women’s involvement in Class I narcotics trafficking and to examine the countermeasures implemented by law enforcement authorities. This research employs an empirical juridical method with a qualitative approach. Data were collected through in-depth interviews with police officers from the narcotics investigation unit of the Tanah Datar Police and a female convicted offender, and were analyzed by relating criminological theories to the local social context. The findings indicate that women’s involvement in narcotics trafficking is influenced by a combination of economic pressure, unequal social relations, and weak social control within their living environments. The countermeasures implemented have included repressive, preventive, and rehabilitative measures; however, they have not yet fully integrated a gender perspective. This study emphasizes that women’s involvement in narcotics trafficking cannot be understood merely as individual legal violations, but rather as a criminological phenomenon shaped by structural and relational conditions. These findings contribute academically to the development of gender-based criminological studies and serve as a reference for the formulation of more comprehensive and gender-sensitive narcotics control policies.